Enhanced Electromagnetic Absorption Properties of Commercial Ni/MWCNTs Composites by Adjusting Dielectric Properties - Zhao, Pei-Yan; Wang, Hui-Ya; Wang, Guang-Sheng (Frontiers in Chemistry, 2020)
In this manuscript, we constructed a Ni/MWCNTs absorber and properly adjusted the permittivity resulted from absorber content in the PVDF to optimize impedance matching properties. Reasonable impedance matching allows electromagnetic waves to propagate into the materials and finally realize energy dissipation through dielectric loss and interfacial polarization. As expected, the maximum reflection loss (RL) of –40.45 dB at 5.20 GHz with a low filler loading (20 wt%) and wide effective bandwidth (RL<–10 dB) of 13.92 GHz in the thickness range of 1.5–5.0 mm was obtained. Our findings offer an effective and industrialized way to design high performance material to facilitate the research in microwave absorption.